Customary Law Perspectives on Preserving Baduy Ulayat Land: A Socio-Legal Study of Sustainability - Fathullah; Robby Nurtresna; Muhamad Wahyudin; Mabsuti; Saifun Nufus (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
This study investigates the pivotal role of customary law (hukum adat) in preserving ulayat (communal) land within the Baduy indigenous community of Indonesia, navigating the complexities of modern legal pluralism. Employing a qualitative socio-legal methodology, this research utilizes purposive sampling involving traditional authorities, specifically the Puun and Jaro. The findings reveal that Baduy land governance is a holistic integration of social, spiritual, and ecological dimensions, in which land is venerated as a sacred ancestral trust (karuhun) rather than a fungible economic commodity. Consequently, traditional norms strictly prohibit land alienation and individual certification. These protective mechanisms are enforced through a sophisticated hierarchical leadership structure in which the Jaro implements both preventive norms and restorative sanctions to maintain communal integrity. Despite formal recognition through regional regulations, this study identifies critical friction between national agrarian policies, external economic pressures, and indigenous autonomy. The research concludes that the Baduy model provides a resilient, sustainable paradigm for land governance. It advocates for a substantive harmonization between state legislation and customary frameworks to ensure the enduring protection of indigenous territorial rights against contemporary developmental encroachment.